PERSEPSI GURU TENTANG KINERJA KEPALA SEKOLAH DASAR NEGERI KECAMATAN GUNUNG TUJUH KERINCI - WENI GUSPARINA (Jurnal Bahana Manajemen Pendidikan, 2018)
Phenomenon in thefield indicatesthat the performanceis doneby the principalin a statethat has not beenideal. This study aimed toobtaininformationaboutteachers' perceptionsaboutthe performance ofthe head ofa public elementary schoolnegerikecamatan gunung tujuh kerinci. This research isdescriptive. The population inthis studyis ateacherwhoisa public elementaryschoolnegerikecamatan gunung tujuh kerinci numbering 81people. The sample inthis study amounted to70 people. by usinga sampling techniqueProportionalRandom Samplingtakenbasedon thetablecrejcie. Data collection toolwas a questionnairewithLikertscale modelthathas been testedfor validity and reliability. Overallaverage score ofteachers' perceptionsaboutthe performance ofthe head ofa public elementary schoolnegerikecamatan gunung tujuh kerinciis3.4. It can be concludedthat the performance ofa public elementary schoolnegerikecamatan gunung tujuh kerincigood enough.